The Impact Of Internet On Undergraduates’ Study Time - Adebisi, Fadhilat Titilayo; Adeyemo, Saheed O. Adeyemi; Oluwafisayo, Abdul (Advances in Social Sciences Research Journal, 2017)
The internet has brought the world to a global village in which one can access almost any kind of information in a blink of an eye. Since the explosion of the Internet in Nigeria and the coming of internet provider coupled with the use of smart phones; schools and colleges have noticed a drop in the amount of study time spent by students. These in some cases have led to poor performance and even a huge dropped out of students in the universities. Kubey et al (2001), showed that 50% of university students were dismissed for academic failure due to excessive use of the internet. In another survey, 283 undergraduates were considered pathological users as a result of their inordinate use of internet. In this view, this study establishes whether internet use affects study time, by investigating the Internet use pattern of undergraduate students and to determine the impact on their study time. The thrust of the paper is that how much impact has the Internet on the study time of the students and their academic use of internet versus social uses of the internet.